Strategi Membangun Budaya Akademik Mahasiswa PGSD Universitas Muhammadiyah Tangerang - Ahmad Arif Fadilah (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
Crucial foundation in shaping students' character, competence, and integrity , particularly within the Elementary School Teacher Education (PGSD) Study Program at Muhammadiyah University of Tangerang. As a higher education institution based on Islamic values, the development of an academic culture not only aims to enhance academic achievement but also to cultivate intellectuals who are religious, critical, creative, and competitive. This article examines comprehensive strategies for building an academic culture among PGSD students at Muhammadiyah University of Tangerang. Academic culture is a fundamental element in producing superior graduates who are intellectual, religious, and possess noble character. The strategies discussed include strengthening character education, building learning communities, optimizing academic facilities, intensive mentoring by lecturers, and fostering a research culture from an early age. Through the integration of these strategies, students are expected to develop critical thinking skills, academic integrity, and high learning motivation. Implementation is carried out through structured programs such as book reviews, national seminars, scientific writing workshops, student writing competitions, and active student involvement in lecturer research. This research employs a qualitative descriptive method with a literature review and empirical observation. The results indicate that collaborative and sustained efforts among lecturers, students, and the institution are key to establishing a resilient academic culture. The success of developing an academic culture relies on harmonious collaboration among all parties, consistent habituation, intensive mentoring, and regular evaluation. It is hoped that this strategy will enable PGSD students to develop into professional teacher candidates who are competent, possess noble character, and have a lifelong learning spirit